2022
DOI: 10.1016/j.idcr.2022.e01422
|View full text |Cite
|
Sign up to set email alerts
|

Rare case of acute transverse myelitis associated with Lyme neuroborreliosis

Abstract: Acute transverse myelitis is a neurological disorder that leads to acute spinal cord injury due to inflammation caused by autoimmune disorders or by parainfectious etiologies. Among the many different infectious causes of transverse myelitis, one of the rare ones is Lyme disease. Here we describe a case of a 62 year old male who presents with bilateral paresthesia and weakness. MRI imaging of the cervical and thoracic spine led to the initial diagnosis of cervical cord edema leading to the symptoms associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The results of our study showed that the rarest and most severe manifestation of early LNB is myelitis, which can result in death due to complications. Despite the rare occurrence, we, like other authors 16,21 , suggest that every patient presenting aseptic encephalitis or myelitis has to be tested for B. burgdorferi s.l. in endemic areas because unfavorable outcomes are possible.…”
Section: Discussionmentioning
confidence: 50%
“…The results of our study showed that the rarest and most severe manifestation of early LNB is myelitis, which can result in death due to complications. Despite the rare occurrence, we, like other authors 16,21 , suggest that every patient presenting aseptic encephalitis or myelitis has to be tested for B. burgdorferi s.l. in endemic areas because unfavorable outcomes are possible.…”
Section: Discussionmentioning
confidence: 50%
“…The results of our study showed that the rarest and most severe manifestation of early LNB is myelitis, which can result in death due to complications. Despite the rare occurrence, we, like other authors 15,20 , suggest that every patient presenting aseptic encephalitis or myelitis has to be tested for B. burgdorferi s.l. in endemic areas because unfavorable outcomes are possible.…”
Section: Discussionmentioning
confidence: 50%